DIFFICULTIES IN TRANSLATION OF METAPHORS - Inomjonova Gulchehra Anvarjon qizi; Batirova Xurshida Egamberdiyevna (PEDAGOGS, 2024)
Abstract. Metaphors are ubiquitous in every nation, culture and language, which presents an influx of challenges for translators because of cultural nuances and abstract meaning. The main of the article is to delve into exploring complexities through examples in source and target languages and analyzing through translation. This article explains the types of metaphors, examples for them and how to make metaphor translation equivalently.